METABOLIC RIDE a conceptual evaluation tool for metabolic biochemistry teaching for graduate and postgraduate students in biological sciences and related areas - Gaeta, Henrique Hessel [UNESP]; Ortolan, Bruna Doimi [UNESP]; Bittencourt Rodrigues, Caroline Fabri [UNESP]; Cruz Costa, Caroline Ramos da [UNESP]; Belchor, Mariana Novo [UNESP]; Toyama, Daniela de Oliveira; Toyama, Marcos Hikari [UNESP] (Soc Brasileira Bioquimica & Biologia Molecular, 2017)
Biochemistry as a discipline have a high degree of difficulty. Otherwise, application of creative games as teaching methodology has spread in various disciplines. METABOLIC RIDE board game is a conceptual and perceptual evaluation tool for biochemistry teaching, aiming to review concepts transmitted in classroom, promoting a competitive challenge to students without denying tools that are at their disposal, stimulating their skills such as their creativity. Further, it makes possible to correlate metabolic routes and their interconnections to establish that metabolic pathways are not separated, such as a railway map. In addition, this game proved to be an excellent tool for student's complementary evaluation, which allowed to analyze the student's perception and thus realize that when properly stimulated some groups could show a great productive and creative capacity. However, this game demonstrated to students new ways to approach complex subjects in biochemistry using creativity.
Keywords: Metabolic map; didactic game; metabolic integration